Effect of carbonization temperature on properties of char from coconut shell - F. Hassan, U.; A. Sallau, A.; O. Ekanem, E.; Jauro, A.; M. Kolo, A. (International Journal of Advanced Chemistry, 2021)
The study Investigate the effect of carbonization temperature on properties of coconut shell. The carbonization was carried out at 600, 800, 1000 and 1150°C temperatures for 1 hour under inert condition. The derived chars were proximately, ultimately and structurally analyzed. The results show that there was a significant change in the volatile matter, fixed carbon percentage, elemental C and its functional group as temperature increases. The moisture content and percentage yield decrease with increasing temperature. The morphological characterization of the materials shows fibrous nature of the raw samples while the char products show developed pores which are suitable for adsorption, movement of electrolyte ions and reduced diffusion resistance. The electrical properties of char improved from 3.52 x10-8 to 6.78 x10-2 S/cm as temperature increases from 600°C to 1150°C. results from X-ray diffractometer analysis showed improved graphitic properties; which suggest a possible use of the char samples particular the PKS1150 in electrode fabrication material.